Asset concentration risk and insurance solvency regulation - Fabian Regele; Helmut Gründl (Goethe University Frankfurt, International Center for Insurance Regulation (ICIR), 2021)
Historical evidence like the global financial crisis from 2007-09 highlights that sector concentration risk can play an important role for the solvency of insurers. However, current microprudential frameworks like the US RBC framework and Solvency II consider only name concentration risk explicitly in their solvency capital requirements for asset concentration risk and neglect sector concentration risk. We show by means of US insurers' asset holdings from 2009 to 2018 that substantial sectoral asset concentrations exist in the financial, public and real estate sector, and find indicative evidence for a sectoral search for yield behavior. Based on a theoretical solvency capital allocation scheme, we demonstrate that the current regulatory approaches can lead to inappropriate and biased levels of solvency capital for asset concentration risk, and should be revised. Our findings have also important implications on the ongoing discussion of asset concentration risk in the context of macroprudential insurance regulation.
Keywords: G01; G11; G22; G28; 330; Microprudential Insurance Regulation; Asset Concentration Risk; Systematic Risk; Idiosyncratic Risk; Sectoral Asset Diversification